2008
DOI: 10.1111/j.1741-3737.2008.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Gay Marriage in States Undergoing Marriage Law Transformation

Abstract: This study examines attitudes toward gay marriage within the context of concern over the weakening of heterosexual marriage. We use data from a three‐state survey conducted in 1998 – 2000 and designed to explore attitudes toward marriage and divorce reform (N = 976). We find that women, Whites, and younger persons are more approving of gay marriage than men, Blacks, and older persons. Nonparents with cohabitation experience are most approving, whereas parents with no cohabitation experience are most opposed. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 42 publications
4
118
1
4
Order By: Relevance
“…Consistently, scholarship indicates that women, higher educated people, non-religious individuals, younger generations, and political liberals are more likely to support pro-LGB policies than men, lower educated people, religious individuals, older generations, and political conservatives (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Pew Research 2013a, 2013b, 2014aRowatt et al 2009;Sherkat et al 2010;Whitehead 2010;Swank et al 2013;Woodford et al 2012). Particularly relevant to the current analyses, scholars have also pointed to regional differences to explain variation in support of pro-LGB policies.…”
Section: Literature Review Public Opinion Of Pro-lgb Policiesmentioning
confidence: 64%
See 1 more Smart Citation
“…Consistently, scholarship indicates that women, higher educated people, non-religious individuals, younger generations, and political liberals are more likely to support pro-LGB policies than men, lower educated people, religious individuals, older generations, and political conservatives (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Pew Research 2013a, 2013b, 2014aRowatt et al 2009;Sherkat et al 2010;Whitehead 2010;Swank et al 2013;Woodford et al 2012). Particularly relevant to the current analyses, scholars have also pointed to regional differences to explain variation in support of pro-LGB policies.…”
Section: Literature Review Public Opinion Of Pro-lgb Policiesmentioning
confidence: 64%
“…Yet such support and acceptance is higher among certain segments of the population than others (Hopkins et al 2013;Moore and Stambolis-Ruhstorfer 2013;Seidman 2002). Studies show that younger people, women, non-religious, and those who know an LGB person support pro-LGB policies at higher levels than other groups (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Rowatt et al 2009;Sherkat et al 2010;Swank et al 2013;Whitehead 2010;Woodford et al 2012).…”
mentioning
confidence: 99%
“…Public opinion studies, however, show that levels of support vary among demographic, political, and religious groups (Baunach, 9 2012;Lewis, 2003;Olson, Cadge, and Harrison, 2006;Pew Research, 2013a;Powell, Yurk Quadlin, and Pizmony-Levy, 2015). Consistently, studies find that women, higher educated people, non-religious individuals, younger generations, and political liberals support same-sex marriage at higher levels than men, lower educated people, religious individuals, older generations, and political conservatives (Andersen and Fetner, 2008;Brumbaugh et al, 2008;Galupo and Pearl, 2007;Haider-Markel andJoslyn, 2005, 2008;Kreitzer, Hamilton, and Tolbert, 2014;Lewis, 2011;Lewis and Gossett, 2008;McCarthy, 2015McCarthy, , 2014Sherkat, de Vries, and Creek, 2010;Whitehead, 2010;Woodford et al, 2012). Also, work has shown that heterosexual people who report having a personal connection to gay, lesbian, and bisexual individuals are more likely to have a positive attitude towards gay rights (Fetner, 2016;Herek, 2002;Herek & Capitanio, 1996).…”
mentioning
confidence: 63%
“…Lubbers, Jaspers, and Ultee (2009) found that the religiosity of the respondents' parents, as well as their attitudes towards homosexuality, are the strongest determinants of attitudes towards same-sex marriage. Evidence of the importance of religion consistently appears in the literature on attitudes towards same-7 sex marriage, especially when taking into consideration religiosity and church attendance (Brumbaugh, Sanchez, Nock, & Wright, 2008;Pearl, & Galupo, 2007;Schwartz, 2010;Sherkat et al, 2011;Walls, 2010).Other studies identify socio-demographic factors that account for attitudes toward same-sex marriage, such as age and political positioning. For instance, the more elderly or politically right wing respondents (Lewis, & Gossett, 2008) or reporting high levels of transphobia/genderism or traditional heterosexism (Moskowitz, Rieger, & Roloff, 2010) display more negative attitudes towards same-sex marriage.…”
mentioning
confidence: 95%
“…Therefore it seemed useful to undertake studies on attitudes concerning samesex marriage at the time of its inception in Portuguese society. sex marriage, especially when taking into consideration religiosity and church attendance (Brumbaugh, Sanchez, Nock, & Wright, 2008;Pearl, & Galupo, 2007;Schwartz, 2010;Sherkat et al, 2011;Walls, 2010).…”
Section: Attitudes Towards Same-sex Marriagementioning
confidence: 99%